XMM-Newton and INTEGRAL Observations of the Bright GRB 230307A: Vanishing of the Local Absorption and Limits on the Dust in the Magellanic Bridge - Sandro Mereghetti; Michela Rigoselli; Ruben Salvaterra; Andrea Tiengo; Dominik P. Pacholski (The Astrophysical Journal, 2023)
GRB 230307A is the second brightest gamma-ray burst detected in more than 50 years of observations and is located in the direction of the Magellanic Bridge. Despite its long duration, it is most likely the result of the merger of a compact binary ejected from a galaxy in the local universe (redshift z = 0.065). Our XMM-Newton observation of its afterglow at 4.5 days shows a power-law spectrum with photon index Γ = 1.73 ± 0.10, unabsorbed flux F _0.3−10 keV = (8.8 ± 0.5) × 10 ^−14 erg cm ^−2 s ^−1 , and no absorption in excess of that produced in our Galaxy and in the Magellanic Bridge. We derive a limit of ${N}_{{\rm{H}}}^{{\rm{HOST}}}\lt 5× {10}^{20}$ cm ^−2 on the absorption at the GRB redshift, which is a factor ∼5 below the value measured during the prompt phase. We searched for the presence of dust scattering rings with negative results and set an upper limit of the order of A _V < 0.05 on the absorption from dust in the Magellanic Bridge.